Using task-modular technologies for physics teaching at petroleum engineering high school - Radis R. Kabirov; Nariman K. Dvoyashkin (Moscow Polytechnic University, 2022)
This paper presents the results of educational research conducted by the Department ofPhysics of Almetyevsk State Petroleum Institute (ASPI) for the organization and effectiveuse of task-modular technology in teaching physics to students of technical universities. The research was aimed at improving the training of qualified bachelors. As a result there is created a system of goals and tasks of different levels developing both physical and mathematical and professional knowledge and skills of students in technical colleges.